Research trends on business strategy formulation: A systematic literature review and bibliometric analysis - Rahman, Arif; Dewayana, Triwulandari Satitidjati; Maulidya, Rahmi; Arafah, Willy (Journal Industrial Servicess, 2025)
Survival in the modern technological landscape demands an effective competitive strategy for every industry, and the offset printing sector is no exception. This study explores trends and future research opportunities in strategy formulation within this specific industry. We utilized a Systematic Literature Review (SLR) methodology complemented by bibliometric analysis. Relevant literature was gathered from sources such as Sciencedirect.com and Publish or Perish version 8, using keywords like "models," "formulation strategies," and "offset printing." Our initial search covered 1,000 articles published between 2014 and 2024. Through a careful screening process, we selected 50 key articles for in-depth evaluation, focusing on their theoretical approaches, applied models, and research methodologies. The analysis revealed two main research streams: quantitative studies often using meta-analysis, and qualitative studies employing comparative cases or in-depth interviews. The field shows diverse models for strategy formulation. Based on our review, we identify 3D printing technology and business model innovation as significant avenues for future research. The bibliometric findings also strongly suggest that offset printing companies should explore integrating new technologies, such as 3D printing, and adopt more flexible, adaptive business models to maintain a competitive edge in today's rapidly changing market.